(untitled) (Nigerian Journal of Technology, 2018)
ABSTRACT Welding processes produce fumes which are known to be dangerous to human health. In order for welders to work in a safe environment, a means of removing these fumes from the welding environment must be provided during the welding process. This is the purpose for which this paper has been developed. Fume extractors are generally known to be fixed to the walls of factories and places where fumes need to be extracted from. With the increase in welding needs outside the workshop environment, the need to have mobile fume extractors has become imperative. This need has been addressed in this paper. Materials for design and fabrication of the fume extractor were selected based on cost, safety, functionality, ease of availability and affordable maintainability. The fabricated fume extractor was tested on several welding sites and found to be very effective in extracting fumes from welders breathing zone. It was also observed that the function of the extractor did not adversely affect the welding process. Keywords: fume extractor, outlet impeller, inlet impeller, radial velocity, fumes. http://dx.doi.org/10.4314/njt.v38i1.15